Post-harvest processing, value-addition and by-product utilisation of nutmeg (Myristica fragrans) - Jayashree, E; PV, Alfiya; K, Anees (Indian Horticulture, 2025)
Nutmeg (Myristica fragrans), a dual spice-yielding tree producing both nutmeg and mace, holds immense commercial potential through post-harvest processing, value addition, and by-product utilization. This paper reviews traditional and improved drying methods, grading standards, and storage practices crucial for maintaining spice quality. It also explores a wide range of value-added products including essential oil, oleoresin, butter, and powders, as well as by-products like nutmeg rind that are being innovatively processed for food and health applications.